Determinants Of Mobile Learning Adoption In The Public Universities In Saudi Arabia: The Mediating Role Of Lecturers’ Attitudes - Saleh S, Alblowi Mansour (2018)
The study attempted to examine the impact of a number of antecedent variables on the adoption of m-learning in the Saudi higher educational context represented by the Saudi public universities. The study also attempted to examine the mediating role of lecturers’ attitudes on the relationship between the antecedent variables and m-learning adoption. Specifically, the study included three main sets of variables, namely the independent variables of lecturers’ capacity, training, readiness, and university commitment, the dependent variable of M-learning adoption, and finally the mediating variable of attitudes towards M-learning.